Establishment of a prediction model for histological chorioamnionitis and its association with outcomes of premature infants - Zhang, Li; Fang, Xin; Li, Zhankui; Han, Xiang; Du, Hongyan; Qu, Pengfei; Xu, Feifei; Wu, Lizhi; Li, Yajun (Frontiers in Pediatrics, 2023)
Aim: To construct a prediction model for histological chorioamnionitis (HCA) and analyze the associations between the predicted risk of HCA and adverse outcomes in preterm infants. Methods: In total, 673 subjects were included in this cohort study and divided into HCA group (n=195) and non-HCA group (n=478). Stepwise method was used for screening the predictors for HCA, and the binary Logistic regression was used to construct the prediction model and the associations between the predicted risk of HCA and adverse outcomes were analyzed. Results: HCA occurred in 195 patients, accounting for 29.0%. The sensitivity of the prediction model was 0.821 (95%CI: 0.767-0.874), the specificity was 0.684 (95%CI: 0.642-0.726), the positive predictive value (PPV) was 0.514 (0.459-0.570), the negative predictive value (NPV) was 0.903 (95%CI: 0.873-0.934), the area under the curve (AUC) was 0.821 (95%CI: 0.786-0.855) and the accuracy was 0.724 (95%CI: 0.690-0.757). The predicted risk of HCA was associated with a higher risk of bronchopulmonary dysplasia (BPD) (OR=3.48, 95%CI: 1.10-10.95), sepsis (OR=6.66, 95%CI: 2.17-20.43), and neonatal infections (OR=9.85, 95%CI: 3.59-26.98), but not NEC (OR=0.67, 95%CI: 0.24-1.88), ROP (OR=1.59, 95%CI: 0.37-6.85) and brain damage (OR=1.77, 95%CI: 0.82-3.83). After adjusting for confounders including gestational week at birth and birth weight, the risk of neonatal infections (OR=5.03, 95%CI: 2.69-9.41) was increased in preterm infants exposure to HCA. Conclusion: The model showed good predictive performance for identifying pregnant women with higher risk of HCA. In addition, HCA was associated with the risk of BPD, sepsis, and infections in neonates.